2016
DOI: 10.3892/ol.2016.4352
|View full text |Cite
|
Sign up to set email alerts
|

The progression of CD56+ myeloid sarcoma: A case report and literature review

Abstract: Abstract.The current study presents a case of cluster of differentiation (CD)56 + myeloid sarcoma in a patient that initially presented with skin lesions, and provides evidence for the clinical and differential diagnosis of myeloid sarcoma. The patient of the present case report was a 65-year-old man who was admitted to hospital with a six-month history of bilateral purple-red papules and nodules, which were present on the upper limbs of the patient and had spread over his whole body one month prior to admissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…However, myeloid sarcoma (MS) is a neoplastic mass formed by immature myeloid cells in the extramedullary position with a low incidence and is more common in children and adolescents ( 5 , 6 ). Studies have shown that ( 7 10 ) MS mainly accumulates connective tissue/soft tissue, and the involvement of the biliary tract is extremely rare. Although inv(16) is a marker of good prognosis, it has been reported ( 11 ) that extramedullary infiltration is also likely to occur in the presence of hyperleukocytes, thrombocytopenia, or gene mutation, mostly in the central nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…However, myeloid sarcoma (MS) is a neoplastic mass formed by immature myeloid cells in the extramedullary position with a low incidence and is more common in children and adolescents ( 5 , 6 ). Studies have shown that ( 7 10 ) MS mainly accumulates connective tissue/soft tissue, and the involvement of the biliary tract is extremely rare. Although inv(16) is a marker of good prognosis, it has been reported ( 11 ) that extramedullary infiltration is also likely to occur in the presence of hyperleukocytes, thrombocytopenia, or gene mutation, mostly in the central nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…e interaction between the invadosome and leukocyte surface B2 integrin could mediate pericellular proteolysis and migration of AML-derived cells into extramedullary tissues [9]. Other adhesion molecules as CD56 have also been associated with higher frequency of MS; however, the exact mechanism involving this molecule is not fully understood [10,11].…”
Section: Discussionmentioning
confidence: 99%